Biological control of Monilinia fructicola (G. Winter) Honey using two isolates of Bacillus subtilis on peaches (2024)
Brown rot of the peach tree caused by Monilinia fructicola affects the genus Prunus in the field, and especially at postharvest, causing losses of up to 60% of the harvested fruits. Brown rot management is currently done using the application of chemical fungicides that generate phytotoxicity in the fruits and contamination in the environment. This increases production costs, demanding the identification of different strategies for disease management. This research aimed to evaluate the biocontrol effects of two isolates of Bacillus subtilis (CB10 and CB11) against M. fructicola using in vitro tests and inoculated fruit versus a chemical control with the dicloran fungicide as a positive control. The inhibition of phytopathogenic growth as well as the severity and rate of inhibition of the M. fucticola were evaluated in dual media. The isolate CB10 in the dual cultures achieved an inhibition rate (biocontrol) of 88.5%, much higher than the other evaluated treatments. In the inoculated fruit this isolate CB10 achieved a rate of inhibition of the pathogen of 95%, higher than other treatments, including the dicloran fungicide. The research allowed us to affirm that B. subtilis CB10 could be used in the biocontrol of M. fructicola for peaches in the management of brown rot disease.